An rGQD/chitosan nanocomposite-based pH-sensitive probe: application to sensing in urease activity assays. (2nd August 2019) - Shi, Fanping; Shang, Danyi; Wang, Zonghua
Abstract : We used the intriguing pH-responsive protonation/deprotonation transitions of chitosan and the fluorescence properties of reduced graphene quantum dots to design a novel pH probe and realize the real-time monitoring of urease activity. Abstract : Herein, we developed a pH sensing platform based on reduced graphene quantum dots (rGQDs) and chitosan (CS). CS was used as the recognition element in the self-assembly of the rGQD/CS nanocomposite because of its fascinating pH-sensitivity, induced by the protonation and deprotonation of the –NH2 group on its edge. The –NH2 was easily protonated under acidic conditions, making CS positively charged. The negatively-charged rGQDs under weak acidic conditions thus could couple with CS through electrostatic attraction, leading to fluorescence quenching. When the pH was changed to basic, the CS became negatively charged, resulting in the disassembly of the rGQD/CS system and causing the system to exhibit a turn-on fluorescence signal. The proposed pH-sensing nanocomposite was successfully applied for sensitive and reliable pH measurements from 5.0 to 9.0. This nanocomposite system was further utilized for the sensitive detection of pH changes caused by the enzymatic activity of urease, thereby proving its utility as a fluorescence turn-on sensor for urease in the field of biochemical and environmental analysis. The photoluminescence (PL) intensity of the rGQD/CS system increased as the pH increased. The increased intensity is directly related to the urease activity in the assay system. Thus, a novel fluorescence turn-on biosensor for urease based on the disassembly of the rGQD/CS composite is proposed. The system response exhibited a nearly linear relationship with urease concentration in the range of 0.05–0.75 U mL −1 . The detection limit for urease was 0.036 U mL −1 . This is the first report of this type of sensor for urease detection. When applied to real sample analysis, the present strategy exhibited satisfactory results.